Analysis on minimally invasive diagnosis and treatment of 49 cases with solitary nodular ground-glass opacity - Zhang, Hu; Duan, Jing; Li, Zhi-Jun; He, Zheng-Fu; Chen, Zhou-Miao; Xu, Yong; Ye, Wei-Wen; Wu, Ou (Journal of Thoracic Disease; Vol 6, No 10 (October 30, 2014): Journal of Thoracic Disease, 2014)
Objective: This study is designed to investigate the treatment approach and prognosis of pulmonary ground-glass-like shadow, especially solitary nodular ground-glass opacity (SNGGO). Methods: Forty-nine cases of SNGGO that persisted after anti-inflammatory treatment in our hospital were retrospectively studied. These patients received thoracoscopic surgery due to indefinitive diagnosis and a tendency of canceration (some cases were followed up for 1-24 months before surgery). Intraoperative rapid frozen section was performed for pathological diagnosis, and surgery method was chosen according to pathological results and the health status of the patients. Results: Forty-three cases showed malignancy, among which 36 cases received thoracoscopic total resection of the lung cancer and seven received simple wedge resection or pulmonary segment resection due to poor lung function; two cases were atypical adenomatous hyperplasia (AAH) and received wedge resection; and four cases were benign and received lesion resection only. Intraoperative frozen section results were in line with postoperative pathological analysis. No lymph node metastasis was detected in any malignant cases as indicated by lymph node dissection or sampling. All malignant cases were staged Ia by postoperative pathological analysis. Neither recurrence nor metastasis occurred during the 1-30 months’ follow-up. Conclusions: SNGGO that persists after anti-inflammatory treatment tend to be adenocarcinoma, which can hardly be diagnosed in the early stage through non-invasive examination. If there’s no contraindication for surgery, video-assisted thoracoscopy (VATS)-guided resection of the lesion plus intraoperative rapid frozen section should be performed to synchronize diagnosis and treatment, which could achieve satisfactory prognosis.